Application of Role Reversal for Adolescent Empathy Development: A Conceptual Analysis and Literature Review - Putri Rahma Cantika; Silvi Gustavio Edward; Delita Wulan Cahyani; Imalatul Khairat (Global Action and Education for Society, 2025)
Role reversal technique is a technique derived from Gestalt theory and psychodrama. Gestalt views existence as something interconnected and uses a holistic counseling approach. This study aims to increase adolescent empathy by encouraging them to see from the perspective of others. By playing different roles, adolescents can significantly increase emotional awareness and empathy skills. This study uses a descriptive qualitative approach with a literature study method that focuses on role reversal research indexed by Google Scholar regarding the development of adolescent empathy in the last 12 years (2013-2025). In this literature study, 3 articles related to the development of adolescent empathy were identified. The results of the study showed that the application of role reversal in social-emotional learning and group guidance services effectively increased empathy and interpersonal relationships in students. The implications of this study indicate that role reversal techniques can be integrated into counseling services and character education programs as an effective strategy to develop empathy and social skills in adolescents in more depth